Higher education leaders' perspectives of accessible and inclusive online learning. Issue 4 (2nd October 2022) - Lomellini, Amy; Lowenthal, Patrick R.; Snelson, Chareen; Trespalacios, Jesús H.
Abstract: Online learning can potentially meet increasingly diverse students' needs in higher education, including disabled students. However, institutions have historically struggled in providing accessible and inclusive online learning. Higher education online learning leaders, those who manage instructional designers, are in a unique position to help institutions strategize and create accessible and inclusive online courses. In this qualitative study, we interviewed nine higher education online learning leaders to understand leaders' perceptions about how institutions provide accessible and inclusive online learning. Results demonstrated that despite varying conceptualizations of accessibility and inclusivity, online learning leaders perceive an insufficient but growing emphasis in higher education. Overall, participants described instructional designers as the most knowledgeable and skilled in this area. Participants described a lack of agency for instructional design teams and a need to advocate for buy-in from senior leadership. They also described strategies (e.g., faculty development, quality standards, and accessibility checkers) to support faculty.